PENERAPAN STRATEGI FORMASI REGU TEMBAK UNTUK MENCAPAI KETUNTASAN BELAJAR SISWA PADA POKOK BAHASAN IKATAN KIMIA DI KELAS X SMA NEGERI 1 KERINCI KANAN, SIAK - Iik Royani Royani; Rasmiwetti '; Miharty ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research was conducted at SMA Negeri 1 Kerinci Righ, Right Kerinci District of Siak which aims to determine how the achievement of mastery learning students with the application of learning strategies firing squad formation rate against chemical subjects on the subject of chemical bonds in class X SMA Negeri 1 Kerinci Right . Experimental class randomly selected from the population . Collecting data in this study using a test technique and direct observation ( observation ) . Aspects assessed in this study include the knowledge , attitudes and skills . The data obtained were processed and analyzed statistically . The results showed that the applied learning strategies can achieve mastery in the classical student learning . Achievement of completeness in the aspect of knowledge  is 85.19 %. Keywords : Mastery Learning , Strategy Formation Team Shoot